2021
DOI: 10.21203/rs.3.rs-312154/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study (GWAS) of seed germination-related traits in rice and identification of candidate genes

Abstract: Background Genome-wide association study (GWAS) has become an accepted and powerful method for understanding the associations between phenotypes and genotypes. In agricultural production, uniform and rapid germination is an important prerequisite in crop production. Here, a rice (Oryza sativa L.) GWAS with 33,934 SNPs (MAF > 0.05) for eight germination traits including germination percentage (GP), shoot (SL) and root length (RL), root (RFW) and shoot fresh weight (SFW), root (RDW) and shoot (SDW) dry weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 128 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Gametic disequilibrium between all pairs of microsatellite loci was tested using POPGENE (Version: 1.32; Panahabadi et al, 2021Panahabadi et al, , 2022Yeh Francis et al, 1999). Null alleles and deviations from Hardy-Weinberg equilibrium for each locus were estimated using Genepop (Version 4.2.1; Panhabadi et al, 2022;Rousset, 2008). Unbiased gene diversity per locus and inbreeding coefficient (F IS ) were estimated using FSTAT (Version 1.2; Goudet, 1995;v.4.2), with the Bonferroni correction provided by FSTAT to infer significant values.…”
Section: Population Genetic Analysismentioning
confidence: 99%
“…Gametic disequilibrium between all pairs of microsatellite loci was tested using POPGENE (Version: 1.32; Panahabadi et al, 2021Panahabadi et al, , 2022Yeh Francis et al, 1999). Null alleles and deviations from Hardy-Weinberg equilibrium for each locus were estimated using Genepop (Version 4.2.1; Panhabadi et al, 2022;Rousset, 2008). Unbiased gene diversity per locus and inbreeding coefficient (F IS ) were estimated using FSTAT (Version 1.2; Goudet, 1995;v.4.2), with the Bonferroni correction provided by FSTAT to infer significant values.…”
Section: Population Genetic Analysismentioning
confidence: 99%
“…There are no reports of GWAS on GABA content in rice; however, GWAS has been used to identify genetic variants associated with numerous phenotypes, including those occurring during germination and seedling growth. Panhabadi et al (2022) reported that the results of GWAS identified several plausible candidate genes for features related to germination and seedling development, which will significantly advance our understanding of the genetic complexity underlying the relevant phenotypes.…”
Section: Discussionmentioning
confidence: 99%